Rhinovirus-induced anti-viral interferon secretion is not deficient and not delayed in sinonasal epithelial cells of patients with chronic rhinosinusitis with nasal polyp - Lee, Sang Hag; Han, Mun Soo; Lee, Tae Hoon; Lee, Da Bin; Park, Jae Hyung; Lee, Seung Hyeok; Kim, Tae Hoon (Frontiers in Immunology, 2022)
Dysregulated innate and adaptive immune response to rhinoviral infection plays an important role in the exacerbation or progressive course of chronic rhinosinusitis (CRS). However, few studies have evaluated whether rhinovirus-induced production of anti-viral interferon is deficient or delayed in inflammatory epithelial cells of patients with CRS with nasal polyps. The aim of the present study is to investigate the replication rates of rhinovirus 16 (RV 16), RV16-induced antiviral interferon secretion, and the expression levels of pattern recognition receptors after RV 16 infection or TLR3 stimulation with poly (I: C) in normal and inflammatory epithelial cells. Inflammatory epithelial cells were obtained from CRS patients with nasal polyps and normal epithelial cells were derived from ethmoid sinus mucosa during endoscopic reduction of blowout fracture or uncinate process mucosa of patients with septal deviation. Cultured cells were infected with RV 16 or treated with poly (I: C) for 24, 48, and 72 h. Cells and media were harvested at each time point and used to evaluate RV16 replication rates, the secretion of IFN-beta, -lambda1, -lambda2, viperin, Mx, and OAS, and the expression levels of TRL3, RIG-1, MDA5, phospho-NFB, and phospho-IRF3. RV replication rates reached peak levels 48 h after inoculation in both normal and inflammatory epithelial cells and showed no difference between both groups of epithelial cells at any time point. The release of IFN-beta, -lambda1, -lambda2 in normal and inflammatory epithelial cells was also strongly induced 48 h after RV16 inoculation but reached peak levels 24 h after poly (I: C) treatment. The expression levels of viperin, Mx, OAS, TLR3, RIG-1, MDA5, phospho-NFB, and phospho-IRF3 showed similar patterns in both groups of epithelial cells. These results suggest that the production of RV16-induced antiviral interferons is not deficient or delayed in inflammatory epithelial cells from CRS patients with nasal polyps.